Yea he will
Adopt that many kittens
Answer:
Step-by-step explanation:
f(-9+h)= (-9+h)² = h²-18h+81
f(-9+h)-f(-9)=h²-18h+81 -81 because : f(-9) = (-9)² = 81
f(-9+h)-f(-9)=h²-18h
(f(-9+h)-f(-9))/h=(h²-18h)/h = h(h-18)/h =h-18
lim (f(-9+h)-f(-9))/h = lim(h-18= - 18
h→0 h→0
Answer:
x= -19
Step-by-step explanation:
2x-4x-9=29
-2x=29+9
x=38/-2
= -19
Answer:
B = 15
Step-by-step explanation:
<u>Combine multiplied terms into a single fraction</u>
6 + 2b/5 = 12
<u>Subtract 6 from both sides</u>
6 + 2b/5 <em>(-6)</em> = 12 <em>(-6) </em>= 2b/5 = 6
<u>Multiply all terms by the same value to eliminate fraction denominators</u>
2b/5 <em>( x 5) </em>= 6<em> (x 5)</em>
<em />
<u>Simplify</u>
2b = 30
Three miles a day should be the correct answer